ALBERT CAMUS AND THE NEOCOLONIAL QUESTION: dialogue between political, artistic and social thoughts - Pereira Spinieli, André Luiz (2024)
Albert Camus was recognized as a philosopher engaged in political and social issues of his time, which took into account the need for liberation of the Franco-Algerian people and the guarantee of rights and citizenship to Algerian Arabs. His philosophy had as its central object the discussion about the absurdity of human existence and its repercussions in different spheres of social life, such as the political and legal levels. My objective is to present the introduction of the neocolonial issue in the thought of Albert Camus, with a view to producing a philosophy that simultaneously dialogues with political, artistic and social categories. His position is controversial and the criticisms made at his time remain valid: by defending the rapprochement between Franco-Algerians and Arabs, instead of complete Algerian independence, the philosopher puts himself in contradiction with his own principles – which defended permanence and fidelity to the debate on the problems of their homeland.